2019
DOI: 10.1590/1807-3107bor-2019.vol33.0102
|View full text |Cite
|
Sign up to set email alerts
|

Reducing social inequalities in the oral health of an adult population

Abstract: The objective of this study was to evaluate the association between social inequality indicators and oral health conditions in an adult population. This prospective cohort study assessed a probabilistic sampling of adults (aged 20-64 years) living in Piracicaba, São Paulo, Brazil. Oral examinations were performed in 2011 and 2015, conducted at home, and used the decay-missing-filled (DMFT) index of permanent teeth, the Community Periodontal Index (CPI), and the visible biofilm criterion. A questionnaire was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(49 reference statements)
0
4
0
1
Order By: Relevance
“…Biological, behavioral, socioeconomic, and environmental factors are associated with dental caries and its consequences [ 2 ]. Socioeconomic status is a distal determinant of dental caries development that modulates exposure to risk and protective factors as well as access to oral health services [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biological, behavioral, socioeconomic, and environmental factors are associated with dental caries and its consequences [ 2 ]. Socioeconomic status is a distal determinant of dental caries development that modulates exposure to risk and protective factors as well as access to oral health services [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, oral health inequalities are increasing in the world with time. Studies conducted in Brazil during 2011-2015 revealed an increasing trend in the prevalence of oral health problems in the country [24]. The oral health-related statistics from Canada and the United States of America have also shown an increasing trend of Oral-health inequalities.…”
Section: St Century and The Oral Heath Related Inequality Trendsmentioning
confidence: 99%
“…Currently, oral health inequality occurs in various parts of the world, including Indonesia. 1,2 The poor condition of dental health in Indonesia is still being reported with a high prevalence of oral health problems. 2,3 Data from Basic Health Research (Riskesdas) 4 revealed the prevalence of dental caries at 88.8% with a DMF-T index of 7.1.…”
Section: Introductionmentioning
confidence: 99%